An emergency space: Herdeiras de Antígona as social and political magnetization (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article is dedicated to thinking about the relations between the performing arts and the urban space from the intervention Herdeiras de Antígona (2019), carried out on the Copan building in São Paulo. The emergency exit of the building takes place on a visible staircase, and the performance presents this space as a metaphor for the urgency of the bodies and speeches of women in contemporary times. The osed reflection is developed through the description and analysis of this creation in the light of the concept of magnetized space found in the writings of visual artist Lygia Pape. When reflecting on the procedures adopted at work, it is evident how this intervention made the inhabitants of the place bring to light the social and political tensions that have marked Brazil since 2016 and, above all, echo feminism agendas as an emergency space.
Keywords: Copan; Magnetized space; Urban Space; Creation’s Procedures; Antigona’s Rereading